From Fatigue to Fitness: A Physician’s Perspective - Sanjay Kalra,; Ananya Rawal,; Meenakshi Verma, (Journal of the Pakistan Medical Association, 2025)
physician’s life. For the physician, fatigue is a multifactorial and multifaceted syndrome. This affects their own health, and that of their patients. Decisions taken during a state of fatigue may be suboptimal, and may lead to undesirable outcomes. We classify fatigue as the 4 Cs – corporeal (bodily), cognitive, communication (vocal) and compassion fatigue. We suggest a simple 5S model to prevent and manage fatigue – Self-awareness, Strengthening oneself, Strengthening the health care system/team, as well as improving Scheduling/Staggering one’s workload, while modifying the Style and strategy of working. Keywords: Fatigue, Tiredness, Self awareness